Gingival giant cell fibroma of unusual size - Carlos Augusto Galvão Barboza (Revista Cubana de Estomatología, 2016)
Giant cell fibroma is a benign oral fibrous tumor and it is typically an asymptomatic sessile or pedunculated mass that is usually less than 1 cm in diameter. The lesion consists of uninflamed fibrous tissue in which there are numerous large uninucleated or multinucleated spindle- and stellate-shaped cells with prominent basophilic cytoplasm. The purpose of this paper is to report a case of a gingival giant cell fibroma of abnormal size. A 31-year-old white woman was referred to the dental service for evaluation of a growth on the mandibular gingival. The intraoral examination revealed a 3.0 × 1.5 cm exophytic gingival mass located in the lingual gingiva of the right mandibular permanent first and second molars. The differential diagnosis included peripheral ossifying fibroma, peripheral giant cell granuloma, and giant cell fibroma. Complete surgical excision of the lesion was performed and the diagnosis of giant cell fibroma was made. No complications or recurrence of the lesion have been noted after 4 years of follow-up. Although giant cell fibromas are benign lesions in which simple surgical excision is curative, it is very important that dental and medical professionals recognize it in light of the frequency of occurrence and the need for a precise diagnosis.